Maintaining Women's Wellbeing: the role of environment and community during the COVID-19 pandemic. Issue 3 (3rd July 2022) - Schech, Susanne; Dodd, Melinda; Saikia, Udoy
ABSTRACT: An online survey conducted in two Australian states (South Australia and Victoria) to study the impact of the pandemic on multi-dimensional wellbeing of individuals found that a higher proportion of women maintained overall wellbeing. Although women reported lower levels of wellbeing in psychological health and similar rates of physical health and living standards compared to men, they achieved higher levels of wellbeing in the ecology and community domains. This paper argues that women's utilisation of blue/green space and social connection played a key role in maintaining wellbeing. Comparing the findings for South Australia and Victoria suggest that women's overall hopefulness and resilience in the pandemic decreased with the severity and length of mobility restrictions.